DISPARITAS PEMIDANAAN DALAM PENYALAHGUNA NARKOTIKA MENURUT UNDANG - UNDANG REPUBLIK INDONESIA NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Christine Isti Hatirindah (to-ra, 2020)
The debate regarding the imposition of criminal penalties for narcotics abusers from a human rights perspective has generated various opinions, both among academics and from legal experts. There are those who agree to the imposition of imprisonment and others who do not agree to imprisonment but provide rehabilitation for narcotics abusers. The punishment of imprisonment for narcotics abusers is a severe punishment and often differs from other decisions, but the evidence presented in court is smaller, but the verdict is considered inadequate due to personal use for oneself and does not victimize others by traded to the crowd. Rehabilitation given to narcotics abusers in Indonesia is still relevant given evidence that can be defended in court and this research can be applied that in the future the formulation, application and implementation of rehabilitation will be given to narcotics abusers who have strong evidence and are given a balance to them. other communities are not selective. Keywords: Disparity, Narcotics, Punishment